Experimental and numerical study on diazinon removal using plasma bubble column reactor: Modeling, kinetics, mechanisms, and degradation products. Issue 5 (October 2022) - Moradi, Hiresh; Kim, Dong-Su; Kim, Se-Hee; Chang, Yoon-Young; Yang, Jae-Kyu; Choi, Eun-Ha; Kamranifard, Telma
Abstract: Diazinone is the most commonly used pesticide worldwide. In this study, experimental and numerical analyses were employed to model and optimize the degradation and mineralization of diazinon using remotely generated non-thermal atmospheric pressure plasma. The initial concentration of diazinon, pH of the medium, and flow rate of the plasma feeding gas were considered as the salient factors in the modeling and optimization processes. To our knowledge, this study is the first report on the effects of gas composition and flow rate on the type and concentration of remotely generated reactive nitrogen and oxygen species (RNOS). An air gas composition was adopted as the feeding gas for a custom-made dielectric barrier discharge (DBD) plasma generator. Remotely generated gas plasma was introduced into the reactor through a diffuser located at the bottom of the column reactor, and the degradation of diazinon and its derived products was monitored using GC-MS. The decrease in the total organic carbon (TOC) content of the samples due to plasma treatment was traced using a TOC analyzer. Although 83.11% degradation was observed, the maximum TOC removal using this method was only 39.22%. Subsequently, response surface methodology (RSM) was employed to mathematically model the process and observe the correlations between different parameters. Our results suggested a quadratic model for the degradation and TOC removal of the given treatment methods, which further indicated that the initial concentration of the analyte and pH influenced the degradation efficiency. However, the gas flow rate was identified as an important factor in TOC removal. The energy yield of the treatment procedure was 46.2 ( g TOC k W − 1 h − 1 ), suggesting the potential of DBD plasma for the treatment of diazinon-polluted water. Graphical Abstract: ga1 Highlights: Detailed explanation for the interaction between RNOS and the aqueous phase. Effect of solubility and surface-active features on diazinon degradation efficiency. Development of optimized quadratic model for diazinon degradation using DBD plasma. Elucidating the effects of plasma feeding gas properties on degradation efficiency.